The Effect of Business Climate on Operations of Small and Medium Scale Enterprises in Nigeria - Joseph Oluremi Olubitan (Bina Nusantara University, 2017)
This research investigated the effect of business climate on operations of Small and Medium Scale Enterprises (SMEs) in Nigeria. Specifically, the aims were to identify the various business climates affecting SMEs, examine how business climates affects sales turnover of SMEs, and evaluate the effect of business climate on Total Factor Productivity (TFP) of SMEs in Nigeria. The research utilized secondary data collected from 2.783 registered businesses in all sectors. The data collected were analyzed using descriptive statistics such as mean and standard deviation. It reveals that majority of SMEs experience one constraints or another as a major obstacle which includes inadequate electricity supply (53,22%) and access to finance (15,74%). Inferential statistics such as Stochastic Frontier Analysis (SFA) indicated that labour (0,9943; P < 0,05) and infrastructure (0,7133; P < 0,05) are the only significant variables to sales turnover. Meanwhile, the regression analysis shows that raw material, labor, infrastructure and fixed cost are the variables that have a strong predicted variance in TFP at P < 0,05 with p-value of 0,000. Water is also observed to be significant at P < 0,1 with p-value of 0,087.